Mechanical and physical properties of dental floss: a comparative cost analysis - Thiago Silva Peres; Izabela Batista Cordeiro; Ianca Daniele Oliveira de Jesus; Roberta de Oliveira Alves; Carlos José Soares; Priscilla Barbosa Ferreira Soares (Bioscience Journal)
The aim of this study was to measure the mechanical and physical properties of 18 commercially available dental flosses produced by global and Brazilian manufacturing and to correlate these parameters with their cost. Eighteen dental flosses available were tested: Bianco Delicare, Colgate, Colgate Menta, Colgate Total, Dauf Oral Care, Hillo, Jade Pro, Johnson and Johnson Essencial, Johnson and Johnson Expansion Plus, Kess, Needs Oral Care, Oral Nexter, Oral-B Essential Floss, Oral-B Pro Saúde, Power Dent Classic Floss, Power Dent Classic Floss Extra Fino, Sanifill Clássico, and Sanifill Infinite. The maximum load (N) and elongation (mm) were measured using a universal testing machine (Instron EL3000). The dental floss width (µm) and filament diameter (µm) were measured using a scanning electron microscope. The cost of each dental floss was correlated with the mechanical and physical properties. The results showed that there was no correlation between the cost of the dental floss and the maximum load (R² = 0.04) or the filament diameter (R² = 0.08). There was a moderate negative correlation between the cost of dental floss and the capacity of elongation (R² = 0.46) and moderate positive correlation between the price and dental floss width (R² = 0.43). It can be concluded that the dental tapes generally cost more per meter and have the lowest elongation capacity. Dental flosses with low cost presented good values for maximum load and elongation, making them suitable for dental hygiene protocols in developing countries.